g(2) = -2(2)

^{2}+ 4 = -8 + 4 = -4So, f(g(2)) = f(-4) = 3(-4) + 2 = -10.

f(2) = 3(2) + 2 = 8

So, g(f(2)) = g(8) = -2(8)

^{2}+ 4 = -128 + 4 = -124Rosie R.

asked • 09/18/18Given f(x) = 3x + 2 and g(x) = -2x2+4

Find f(g(2))

What would you do in order to solve? Explain in words the process to solving f(g(2)). How is that different than g(f(2))?

Find f(g(2))

What would you do in order to solve? Explain in words the process to solving f(g(2)). How is that different than g(f(2))?

I really don't understand this question or how to do problems like this. I've tried to look online, but don't even know what to search. Thank you for your help!

More

g(2) = -2(2)^{2} + 4 = -8 + 4 = -4

So, f(g(2)) = f(-4) = 3(-4) + 2 = -10.

f(2) = 3(2) + 2 = 8

So, g(f(2)) = g(8) = -2(8)^{2} + 4 = -128 + 4 = -124

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.

Rosie R.

09/18/18